PENGARUH DOSIS PUPUK NPK TERHADAP PERTUMBUHAN BIBIT JABON MERAH (Anthocephalus macrophyllus) PADA MEDIA CAMPURAN TANAH PMK, KOMPOS DAN PASIR - Sukarminingsih, .; AM, Iskandar; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2017)
The red jabon (Anthocephalus macrophyllus) is one type that has an important role in the forest and land rehabilitation activities, beacause the cycle is shorter so it can provide high production in short time. The purpose of this research is to get the dose of appropriate NPK fertilizer for the red jabon growth on mixed media ultisol soil, compost and sand. The problem is how many doses of NPK fertilizer should be given to the plant. This research is an experimental research prepared using Completely Random Design methode that which consisted of 6 treatment with 4 replication so there is a 24 unit experiments. Treatment without fertilizer is control (P0), fertilizer treatment of NPK with the dose 0,5 g plant/(P1), fertilizer treatment of NPK with the dose 1 g/plant (P2), fertilizer treatment of NPK with the dose 1.5 g/plant (P3), fertilizer treatment of NPK with the dose 2 g/plant (P4), fertilizer treatment of NPK with the dose 2,5 g/plant (P5). The result of researchÂ  showed treatment of giving NPK fertilizer with the kinds of dose on the red Jabon seed with mix media of ultisol soil, compost and sand (2:1:1) not yet the real effect to height, diameter and number of leaves.Keywords: compost, NPK, red jabon.